2002
DOI: 10.1097/00000542-200201000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parecoxib, a Parenteral COX-2-specific Inhibitor, on the Pharmacokinetics and Pharmacodynamics of Propofol

Abstract: Single-bolus parecoxib, in doses to be used perioperatively, does not alter the disposition or the magnitude or time course of clinical effects of bolus propofol. Effects on a propofol infusion were not evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…However, valdecoxib may suppress P-450 2C9 (CYP2C9). 30 On the other hand, it has been reported that P-450 induced by aspirin generates both 15-R-HETE (40%, which is converted to 15-epi-LXA 4 ) and 15-S-HETE (60%, which is converted to lipoxin-A 4 ). 26 Indeed, it was demonstrated that aspirin augmented the generation of both lipoxins and 15-epi-lipoxins in human lung adenocarcinoma cell line.…”
Section: · Dmentioning
confidence: 99%
“…However, valdecoxib may suppress P-450 2C9 (CYP2C9). 30 On the other hand, it has been reported that P-450 induced by aspirin generates both 15-R-HETE (40%, which is converted to 15-epi-LXA 4 ) and 15-S-HETE (60%, which is converted to lipoxin-A 4 ). 26 Indeed, it was demonstrated that aspirin augmented the generation of both lipoxins and 15-epi-lipoxins in human lung adenocarcinoma cell line.…”
Section: · Dmentioning
confidence: 99%
“…Drug interactions between valdecoxib and many other drugs have been extensively studied [35,36]. Of particular interest is the fact that valdecoxib does not significantly affect the action of methotrexate.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…This drug has been approved for the treatment of rheumatoid arthritis, osteoarthritis and pain [113][114][115]. Valdecoxib is metabolized primarily by cytochrome P450 2C9 and 3A4 to the pharmacological active hydroxylated metabolite and the carboxylic acid metabolite in humans [116][117][118]. Chemical structures of valdecoxib, hydroxylated valdecoxib, and carboxylic acid valdecoxib are shown in Fig.…”
Section: Valdecoxibmentioning
confidence: 99%